On providence and other essays - Zwingli, Ulrich, 1484-1531; Jackson, Samuel Macauley, 1851-1912.; Hinke, William John, 1871-1947 (Durham, NC Labyrinth, 1922)
Includes index.
Reprint (1983). Originally published : The Latin works and the correspondence of Huldreich Zwingli, volume two, with varient title : The Latin works of Huldreich Zwingli, volume two.-- Philadelphia, PA : Heidelberg Press, 1922.
Keywords: Zwingli, Ulrich, -- 1484-1531; Theology -- addresses, essays, lectures